The Attitude of British Diplomats in Iraq Towards Arab Issues: Kuwait as a Case Study (1932- 1939) - Rashid Makaeel Muhammed; Shakhawan Abdullah Saber (Zanco Journal of Humanity Sciences)
The British were busy with controlling the Gulf region for strategic, economic, and political reasons, especially Iraq and Kuwait, which Britain looked into. Britain also played a role in the path of Arab and regional issues, where Iraqi-Kuwaiti relations witnessed political tensions and in several occasions. The Iraqi official authorities informed the British embassy that Kuwait constitutes an obstacle to Iraq's arrival in the sea, and there are official Iraqi statements that Kuwait is affiliated with Iraq.